Old Macdonald's things that go - Clarke, Jane (London : Nosy Crow, 2020)
This raucous, read-aloud picture board book is perfect for any child who loves farmyard animals and vehicles!Old Macdonald's farm is full of pigs, cows, sheep, hens and horses, but what he really loves is his COLOSSAL collection of vehicles!
Keywords: Board book; Children's stories; Pictorial works; Stories in rhyme